Pengembangan Media Pebelajaran Audio Visual Berbantuan Adobe Flash dan Android Pada Kompetensi Dasar Mengelola Arsip Elektronik untuk Kelas X OTKP1 SMK Negeri 2 Blitar - Ahmad Jauhari Musthofa; Jaka Nugraha (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This development research aims to describe the process of developing Audio Visual learning media assisted by Adobe Flash and Android in Basic Competence in Managing Electronic Archives for Class X OTKP 1 SMK NEGERI 2 Blitar, analyzing the feasibility of developed learning media and analyzing students' responses to learning media that have been developed. This research uses research and development methods and uses the 4-D development model. The sample used for the limited trial was 20 students in class X OTKP 1 SMK NEGERI 2 Blitar. The data collection instruments used material expert validation sheets, media expert validation sheets and student response sheets. All validation sheets and student response sheets use a Likert scale. The product produced in this research development is in the form of android based audio visual learning media which contains material, voice narration, multiple choice questions with automatic assessment, and practical assignments to store records electronically in accordance with the basic competencies in managing electronic records. The results of the assessment by material validation experts were 86% with "very proper" interpretations, and media experts by 81% with "very decent" interpretations. assessment obtained from trials is limited to students by 85% with the interpretation "very feasible". These results indicate that the audio visual learning media assisted by Adobe Flash and Android on the basic competence of Managing Electronic Archives is declared suitable for use in the learning process in class X OTKP 1 SMK NEGERI 2 Blitar.